PEMBELAJARAN SISTEM PRODUKSI RAMPING BERBASIS SIMULASI DALAM KURIKULUM PROGRAM STUDI SARJANA MANAJEMEN REKAYASA - NIKO SARIPSON SIMAMORA (JURNAL ILMIAH MAKSITEK, 2019)
Practical learning in a laboratory enhances the experience of the students in order to comprehend the understanding about the concepts of science learned in a class. The Undergraduate Engineering Management Study Program at the Institut Teknologi Del develops a curriculum that combines either practical understanding or basic concepts in learning. In particular, the production system course as an integral part of industrial engineering. This paper aims to describe the learning process of a lean production system for students on simulation-based learning. The simulation-based learning process is carried out in a laboratory developed and adopted from the concept of lean production system. The lean production systems developed from the automotive production system in Japan could be seen as a successful implementation and development of industrial engineering concepts. In the future, the concept of lean production systems is not limited only on a manufacturing domain, but can be developed into other industries.